(untitled) (Research, Society and Development, 2020)
The objective of this study was to determine the crude protein requirements for juvenile jundiara fish, a hybrid of Pseudoplatystoma fasciatum X Leiarius marmoratus. A total of 240 juveniles of the hybrid, with an initial mean weight of 8.4 ± 1.41 g, were distributed in 15 fiberglass tanks (170 L) in a closed water recirculation and constant aeration system, with a density of 16 fish/tank. The experimental design was completely randomized with five treatments and three replications. The treatments consisted of diets with 32, 34, 36, 38 and 40% crude protein. Seventy days into the experiment the final fish weight and feed intake were measured. Two specimens from each experimental unit were collected for evaluation of carcass chemical composition, nutritional efficiency and blood parameters. The increase in crude protein content promoted the significant, increasing linear effect for mean weight gain, mean feed intake and specific growth rate, and decreasing effect for feed conversion. Significant differences were also observed in carcass chemical composition, nutritional efficiency, total plasma protein, glucose, cholesterol, triglycerides and lipase enzymatic activity. Thus, the increase in crude protein levels of up to 40% in jundiara diets promotes improvement in the productive performance of juvenile jundiara.